On-Chip Organoid Formation to Study CXCR4/CXCL-12 Chemokine Microenvironment Responses for Renal Cancer Drug Testing - Adem Ozcelik; Burcin Irem Abas; Omer Erdogan; Evrim Cevik; Ozge Cevik (Biosensors, 2022)
Organoid models have gained importance in recent years in determining the toxic effects of drugs in cancer studies. Organoid designs with the same standardized size and cellular structures are desired for drug tests. The field of microfluidics offers numerous advantages to enable well-controlled and contamination-free biomedical research. In this study, simple and low-cost microfluidic devices were designed and fabricated to develop an organoid model for drug testing for renal cancers. Caki human renal cancer cells and mesenchymal stem cells isolated from human umbilical cord were placed into alginate hydrogels. The microfluidic system was implemented to form size-controllable organoids within alginate hydrogels. Alginate capsules of uniform sizes formed in the microfluidic system were kept in cell culture for 21 days, and their organoid development was studied with calcein staining. Cisplatin was used as a standard chemotherapeutic, and organoid sphere structures were examined as a function of time with an MTT assay. HIF-1α, CXCR4 and CXCL-12 chemokine protein, and CXCR4 and CXCL-12 gene levels were tested in organoids and cisplatin responses. In conclusion, it was found that the standard renal cancer organoids made on a lab-on-a-chip system can be used to measure drug effects and tumor microenvironment responses.